Biocomposite from Epoxidized Soybean Oil and Microfibrilled Cellulose - Naokichi Imai; Antonio Norio Nakagaito; Hiroyuki Yano; Hiroshi Uyama (Wood Research Journal, 2013)
In this study, a biocomposite consisting of an oil-based network polymer and microfibrillated cellulose (MFC) have been prepared and its mechanical and thermal properties have been evaluated. Epoxidized soybean oil (ESO) was impregnated in a mat of MFC, followed by the acid-catalyzed curing of ESO to produce the biocomposite. SEM observation shows the good dispersion of the cellulose fiber in the oil-based network polymer. The Young's modulus and tensile strength of the biocomposite were much superior to those of the ESO homopolymer and these values increased as a function of the MFC content in the biocomposite. The storage modulus (E’) of the biocomposite in the rubbery region was also larger than that of the ESO homopolymer.